Se\~noreaje cercano al límite y acumulación de vulnerabilidad financiera en moneda extranjera: Bolivia, periodo 2009 - 2024 junio - Nano Luis Silva (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2024)
Seigniorage is the ability of a central bank to capture real resources from the economy through the creation of nominal primary money. This article investigates the conditions of financial vulnerability in foreign currency of the BCB that would limit its essential functions as lender of last resort and safeguard of economic and financial stability. The main results show that seigniorage approached itslimit levelsin recent years when a growing gap wasrecorded between effective international reserves and a recommended threshold associated with an eventual balance of payments crisis; when the measures to support the BCB's international reserves compromised a risky decumulation of liquid assets in foreign currency held by the banks; and, when access to international debt markets was narrowed.
Keywords: E44; E58; E63; F34; 330; Seigniorage; Financial vulnerability in foreign currency; International reserves gap